2022
DOI: 10.11648/j.fem.20220801.11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Bacteria on Automated Teller Machines (ATMs) in Makurdi Metropolis

Abstract: The automated teller machine (ATM) has been an important device in the banking sector and other financial institutions. The aim of this study was to isolate and identify Bacteria on the keypads of selected Automated Teller Machines (ATMs) in Makurdi metropolis. Swab sticks soaked with sterile normal saline were used to collect specimens from the keypads of the ATMs. The swab sticks were immediately transferred to the laboratory of Microbiology in the Department of Biological Science, Benue State University Mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…It occurrence. This result is in agreement with a could also be credited to cross-contamination previous study (Awua et al, 2022), which from various human activities such as touching reported a 43% and 47% prevalence of E.coli the ATM keypads, coughing, sneezing, and respectively. This clearly suggests that the ATMs talking during the process of using the ATM; may be frequently contaminated with faeces.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It occurrence. This result is in agreement with a could also be credited to cross-contamination previous study (Awua et al, 2022), which from various human activities such as touching reported a 43% and 47% prevalence of E.coli the ATM keypads, coughing, sneezing, and respectively. This clearly suggests that the ATMs talking during the process of using the ATM; may be frequently contaminated with faeces.…”
Section: Discussionsupporting
confidence: 93%
“…This finding prevalence, although Ya'aba reported a lower corroborates a previous study (Agu et al, 2018), prevalence of Klebsiella pneumoniae in his which reported that exposure to many users, study. Isolating Klebsiella from the keypad of environmental components like rain, and ATMs may present a public health risk to users climatic elements such as wind may be who do not wash their hands after using these responsible for the high microbial load on the machines (Okoro et al, 2018). Findings from keypad of ATMs.…”
Section: Discussionmentioning
confidence: 99%
“…The result is consistent with the study of Dawodi and Akanbi [14], which identified bacteria from automated teller machines on the Federal Polytechnic Ede campus that are skin commensals (Staphylococcus and Micrococcus), environmental bacteria (Serratia and Pseudomonas), and intestinal bacteria (Salmonella and Klebsiella). This result is also in line with the work of Awua Yuana et al [15], who isolated Staphylococcus aureus (41.6%), Escherichia coli (34.4%), and Klebsiella pneumoniae (24.0%) on the keypads of the ATMs.…”
Section: Staphylococcus Aureus Is a Common Componentsupporting
confidence: 91%